(untitled) (World Bulletin of Management and Law, 2022)
Most-favored-nation clause is of great importance in international law in general, and in investment in particular, as it represents the best guarantees established for the benefit of the investor. This condition raises legal issues in the international framework, including what is related to the scope of its application in substantive and procedural provisions and the role of arbitral tribunals’ practices In the development of many concepts related to this condition